Physiological response of rabbit bucks to dietary fumonisin: Performance, haematology and serum biochemistry - Ewuola, E.O.; Gbore, F.A.; Ogunlade, J.T.; Bandyopadhyay, Ranajit; Niezen, J.; Egbunike, G.N. (Springer, 2008)
Maize grains contaminated with fumonisin, a metabolite of Fusarium verticillioides was incorporated into matured male rabbits' diet to evaluate its effects on performance, haematology and serum biochemistry in rabbits. Thirty individually caged crossbred adult rabbit bucks averaging 1.36 ± 0.01 kg (about 22-24-week-old) were randomly allotted to three treatment diets comprising a control diet (containing 0.35 ± 0.02 mg fumonisin/kg) and two test diets containing 12.30 ± 0.16 and 24.56 ± 0.14 mg fumonisin/kg, constituting treatments 1 (low infection), 2 (medium infection) and 3 (high infection), respectively, in a five-week feeding trial. Results showed that the dry matter intake (DMI) (g/rabbit) at the end of the feeding trial was significantly (P < 0.05) influenced. The DMI declined with increasing dietary fumonisin by a significant 80% and 95% (P < 0.05) for high and medium levels of dietary fumonisin, respectively, relative to the mean weekly DMI of 609.93 ± 45.08 g by rabbits fed diet with low level of fumonisin. The weekly weight gain tended to decrease with increased dietary fumonisin levels, while the haematological and serum biochemical components examined, were not statistically influenced among the diets when fed to male rabbits for a period of 5 weeks.